Search Algorithm: Essence of Optimization (IntechOpen, 2023)
Algorithms, particularly those embedded in search engines, social media platforms, recommendation systems, and information databases, play an increasingly important role in selecting what information is most relevant to us, which is a crucial feature of our participation in public life. These algorithms are not just helpful in our daily lives but are also one of the unavoidable necessities of modern living. This book discusses advances and applications of various types of search algorithms, such as quantum search, harmony search, cognitive search, genetic search, and many others. It is a valuable resource and provides a solid technical base for frontline investigations of search algorithms for scientists and students interested in search and optimization methods.